SERVICE-ORIENTED APPROACH FOR OPTIMAL ROUTING OF INFORMATION FLOWS IN MULTISERVICE NETWORKS - N. I. Listopad; A. A. Haider; S. Yu. Michnevich (Системный анализ и прикладная информатика)
New approach for optimal routing of information flows is developed based on service-oriented architecture. To find the shortest path it’s require to take into account the QoS-parameters such as delay, jitter, bandwidth, lost of the packets and cost of telecommunication resources.